PERBANDINGAN EFEK KERUTAN TIGA DIMENSI PADA RIAS WAJAH KARAKTER TUA MENGGUNAKAN TISU WAJAH DAN LATEX DENGAN TISU WAJAH DAN LEM BULU MATA - Fhadila Yunalis; Merita Yanita (Universitas Negeri Padang, 2022)
This research is backgrounded because students are not taught about the makeup of three-dimensional old characters, where the result of wrinkles from the makeup of threedimensional old characters is more visible and natural. The study aims to analyze 1) how the effect of three-dimensional wrinkles on the facial makeup of old characters using facial and latex wipes, 2) how the three-dimensional wrinkle effect results on the makeup of the old character using facial wipes and eyelash glue, 3) how the three-dimensional wrinkle effect compares to the facial makeup of the old character using facial and latex wipes using facial wipes and eyelash glue. This research uses pseudo-experimental research methods (quasi experiments). This research variable is a free variable (X), a bound variable (Y). The data type uses primary data. The data collection techniques in this study are observations, documentation, instruments. The steps to analyze the data are test analysis requirements, hypothetical tests. Based on the results of study 1) the effect of three-dimensional wrinkles on the makeup of old characters using facial and latex wipes from the neat aspect shows an average of 1.90 untidy categories, resilience showed an average of 2.19 categories were less precise and from the resilience aspect showed an average of 2.62 categories less resistant, 2) the result of three-dimensional wrinkle effects on the makeup of old characters using facial wipes and eyelash glue from the neat aspect showed an average of 3.29 neat categories , resilience shows an average of 3.19 categories of resistance and from the durability aspect shows an average of 3.10 resistant categories, 3) there is a comparison of neatness, accuracy and durability of the threedimensional wrinkle effect on the makeup of older characters using facial and latex wipes with facial wipes and eyelash glue. It is then recommended for students to add knowledge in doing three-dimensional old character makeup by using facial and latex wipes with facial wipes and eyelash glue